Data Management in Grid and Peer-to-Peer Systems - Hameurlain, Abdelkader (Springer, 2017)
This book constitutes the refereed proceedings of the First International Conference on Data Management in Grid and Peer-to-Peer Systems, Globe 2008, held in Turin, Italy, in September 2008. P2P and grid computing are important for scale distributed systems and applications that require effective management of voluminous, distributed, and heterogeneous data.